Beclin 1 deficiency is associated with increased hypoxia-induced angiogenesis - Lee, Seon-Jin (Landes Bioscience, 2011)
Beclin 1, a tumor suppressor protein, acts as an initiator of autophagy in mammals. Heterozygous disruption of Beclin 1 accelerates tumor growth, but the underlying mechanisms remain unclear. We examined the role of Beclin 1 in tumor proliferation and angiogenesis, using a primary mouse melanoma tumor model. Beclin 1 (Becn1(+/−)) hemizygous mice displayed an aggressive tumor growth phenotype with increased angiogenesis under hypoxia, associated with enhanced levels of circulating erythropoietin but not vascular endothelial growth factor, relative to wild-type mice. Using in vivo and ex vivo assays, we demonstrated increased angiogenic activity in Becn1(+/−) mice relative to wild-type mice. Endothelial cells from Becn1(+/−) mice displayed increased proliferation, migration and tube formation in response to hypoxia relative to wild-type cells. Moreover, Becn1(+/−) cells subjected to hypoxia displayed increased hypoxia-inducible factor-2α (HIF-2α) expression relative to HIF-1α. Genetic interference of HIF-2α but not HIF-1α, dramatically reduced hypoxia-inducible proliferation, migration and tube formation in Becn1(+/−) endothelial cells. We demonstrated that mice deficient in the autophagic protein Beclin 1 display a pro-angiogenic phenotype associated with the upregulation of HIF-2α and increased erythropoietin production. These results suggest a relationship between Beclin 1 and the regulation of angiogenesis, with implications in tumor growth and development.